Get it on Google Play
Q.1 Solve
i) \( 2 - \frac{3}{5} \)
ii) \(4 + \frac{7}{8} \)
iii) \( \frac{3}{5}+\frac{2}{7} \)
iv) \( \frac{9}{11}-\frac{4}{15} \)
v) \(\frac{7}{10}+\frac{2}{5}+\frac{3}{2} \)
vi) \(2\frac{2}{3}+3\frac{1}{2} \)
vii) \(8\frac{1}{2}-3\frac{5}{8} \)
Answer :

(i) \( 2- \frac{3}{5} = \frac{2×5-3}{5}= \frac{7}{5} = 1\frac{2}{5} \)
ii) \(4 + \frac{7}{8} = \frac{8×4+7}{8}= \frac{39}{8}=4\frac{7}{8} \)
iii) \(\frac{3}{5}+\frac{2}{7} = \frac{7×3+5×2}{35}=\frac{21+10}{35}= \frac{31}{35} \)
iv) \(\frac{9}{11}-\frac{4}{15}=
\frac{15×9-11×4}{165}= \frac{135-44}{165}= \frac{91}{165}\)
v) \(\frac{7}{10}+ \frac{2}{5}+\frac{3}{2} = \frac{7×1+2×2+3×5}{10}=
\frac{7+4+15}{10} =\frac{26}{10} =\frac{26÷2}{10÷2} =\frac{13}{5} =2\frac{3}{5} \)
vi) \( 2\frac{2}{3}+3\frac{1}{2} =
\frac{8}{3}+\frac{7}{2}= \frac{2×8+3×7}{6}= \frac{16+21}{6}=\frac{37}{6}= 6\frac{1}{6} \)
vii) \( 8\frac{1}{2}-3\frac{5}{8} = \frac{17}{2}-\frac{29}{8}= \frac{17×4-29×1}{8}= \frac{68-29}{8} = \frac{39}{8} =4\frac{7}{8} \)